International journal of professional business review (University of Corun̋a, Faculty of Economics and Business, 2016)
"... aims to publish original research in order to contribute to the promotion and dissemination of key issues in professional business and academia. The JPBReview's content aspires to be relevant and interesting to a wide readership, which adds to the understanding and discussion of professional business and academia worldwide. To be published in the JPBReview, authors must adhere to high standards of research and contribute to theory and/or practice in related areas, regardless of whether the level of analysis is the organization, region or country."--Website, viewed October 26, 2018.